INVESTIGATING THE SUPPLY SIDE DETERMINANTS OF BLOCKCHAIN TECHNOLOGY ADOPTION FOR ENTREPRENEURIAL FINANCING- A TWO STAGED APPROACH - Mcintosh Mufunani Kuhlengisa; CHUKUAKADIBIA ERESIA-EKE (IJEBD (International Journal of Entrepreneurship and Business Development))
Access to financing is vital for the growth of entrepreneurial firms in emerging economies like South Africa. Technological innovations such as blockchain can reduce transaction costs and disrupt traditional models, offering benefits like reliability, trust, security, and efficiency. However, adoption barriers persist, including infrastructure limitations and the emerging nature of the technology. This study employs a quantitative approach to investigate factors affecting the adoption of blockchain technology among employees of entrepreneurial financing firms through an online survey. Using Partial Least Squares Structural Equation Modelling and Artificial Neural Network Analysis (PLS-SEM ANN), the findings indicate that facilitating conditions, social influence, anxiety, and attitude significantly impact the behavioral intention to adopt blockchain, while effort expectancy, performance expectancy, and self-efficacy do not. The study recommends creating supportive environments, leveraging social networks, addressing anxiety, and fostering positive attitudes toward blockchain. It suggests investing in infrastructure, increasing awareness of blockchain benefits, improving communication to alleviate anxieties, and showcasing success stories to enhance adoption